2014
DOI: 10.1039/c3mb70387h
|View full text |Cite
|
Sign up to set email alerts
|

Conditional protein splicing of α-sarcin in live cells

Abstract: Protein splicing technology harnesses the ability of inteins to ligate protein fragments, forming a mature protein. This report describes our effort to engineer rapamycin-dependent protein splicing of a ribotoxin, called α-sarcin. Engineering this system required the investigation of important splicing parameters, including extein context and splicing temperature. We show α-sarcin splicing is dependent on rapamycin, is inducible with rapid kinetics, and triggers apoptosis in HeLa cells. These findings establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, there are some exceptions to this rule. For example, the artificially split Sce VMA intein can undergo PTS without a refolding step if (and only if) the two fragments, VMA N and VMA C , are brought into proximity using a two- or three-hybrid paradigm (Figure b). In another example, Mootz and co-workers demonstrated that the artificially split Ssp DnaB intein can effect PTS under native conditions, albeit with reduced efficiency compared to the parental contiguous intein (Figure c) …”
Section: Protein Trans-splicingmentioning
confidence: 99%
“…However, there are some exceptions to this rule. For example, the artificially split Sce VMA intein can undergo PTS without a refolding step if (and only if) the two fragments, VMA N and VMA C , are brought into proximity using a two- or three-hybrid paradigm (Figure b). In another example, Mootz and co-workers demonstrated that the artificially split Ssp DnaB intein can effect PTS under native conditions, albeit with reduced efficiency compared to the parental contiguous intein (Figure c) …”
Section: Protein Trans-splicingmentioning
confidence: 99%
“…Close proximity then allows the inteins to fold and activate splicing ( Figure 1B). This approach, for which the term 'conditional protein splicing (CPS)' was actually coined, was applied in a variety of ways, for example in vitro for the control of an artificially autoinhibited protein kinase (Mootz et al, 2004), to activate tobacco etch virus (TEV) protease in yeast cells (Sonntag and Mootz, 2011), to induce apoptosis in mammalian cells via the RNAse α-sarcin (Alford et al, 2014) and to regulate firefly luciferase in living fruit flies, which showed detectable luciferase activity as early as 10 to 20 min after exposure to rapamycin-containing food (Schwartz et al, 2007) (see Table 1 for more examples of ligand-controlled Sce VMA intein).…”
Section: Methods To Control Split Inteinsmentioning
confidence: 99%
“…The reporter protein functions can be inducibly controlled by enzymes, [6] chemical compounds, [7] ions, [8] light, [9] and so on. To this end, inteins, which are single‐turnover enzymes catalyzing protein splicing, [10] have been used [11–15] . Naturally occurring inteins are categorized into three groups: inteins that have a homing endonuclease between the splicing domains, inteins that have only a splicing domain, and inteins that catalyze splicing in trans (protein trans ‐splicing; PTS) through split inteins.…”
Section: Introductionmentioning
confidence: 99%